Common Genetic Variants of the Mitochondrial Trafficking System and Mitochondrial Uncoupling Proteins Affect the Development of Two Slowly Developing Demyelinating Disorders, Leukoaraiosis and Multiple Sclerosis - Szolnoki, Z. (Current Medicinal Chemistry, 2010)
As the central energy source, the mitochondria are of great importance in the maintenance of the glia cells of the brain. It is presumed that mitochondrial energy production is affected not only by wellndash characterized genetic mutations of the mitochondria, which are associated with severe malfunctions and resultant acute glia and neuronal cell death, but also by a number of other unfavorable genetic variants. The genetic variants of the kinesin motor proteins and mitochondrial uncoupling proteins (UCPs) are believed to influence the mitochondrial energy production in different distress states of the glia cells. The kinesin motor proteins carry the mitochondria from the central parts to the peripheral parts of the glia cells, where myelin protein synthesis takes place. The UCPs are essential for regulation of the mitochondrial membrane potential under different physiological conditions, thereby finally attuning mitochondrial energy production in environmental states such as cold exposure, fasting or chronic mild hypoxia. While the capacity of the kinesin motor proteins can affect the number of mitochondria in the peripheral parts of the glia cells, the functional features of the UCPs can affect the degree of energy production of the mitochondria by influencing the mitochondrial membrane potential. The different genetic variants may display different activities, and some may result in a slowly developing energy shortage in the glia cells. In this context, this article discusses the roles of genetic variants of the kinesin motor proteins and UCPs in slowly developing diseases of the white matter of the brain as multiple sclerosis and leukoaraiosis.
Keywords: multiple sclerosis